The Study of Thin Layer Drying Model of Chili - Pratummasoot, Noppamas; Mundpookier, Tawedach (Journal of Applied Research on Science and Technology (JARST), 2021)
The objective of this research was to study a thin layer drying model as an efficient mathematical model in order to determine the optimize model to study the relationship between the ratio of moisture and the time for chili. The researcher brought chili, which has a mass and initial moisture value, in the range of 42-52 g and 330-380%, d.b., respectively. Then, it drying with temperature control equal to 50ºC, 60ºC and 70ºC, and the relative humidity values of air were 10%, 20% and 30% at wind speed equal to 1 m/s. There will be a total of 9 trials. The dryer used in this experiment consisted of two main parts: 1) the relative humidity control of the air inside the machine, which is a glass chamber and ceramic packed system for producing saturated air, and 2) the control section temperature which is a temperature control button on the outside and temperature can be adjusted as needed. The experimental results found that the last moisture content ranges from 6-8%, d.b. Then, the results of the experiments were then used to calculate the moisture content and moisture ratio from the chili experiments for calculation and compared to the moisture ratio obtained from a total of 6 models. According to the results of the model’s accuracy test, the models suitable for chili for all temperatures and humidity were the Wang and Singh models, which yielded differences in the form of RMSD and MBD in the range of 2.78 – 6.86% and -0.20 – 2.95%, respectively.